Návrh zdokonalení marketingového mixu společnosti - Dubský, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Tato bakalářská práce se zabývá návrhem zdokonalení marketingového mixu společnosti, konkrétně Hotelem Červenohorské sedlo. V teoretické části jsou objasněny pojmy marketing, marketingový mix, marketingové prostředí, SWOT analýza a Porterova analýzy. V analytické části je popsán samotný hotel, dále jsou provedeny analýzy marketingového prostředí, ve kterém se hotel nachází. Dále jsou provedeny analýzy SWOT a Porterova analýza. Výstupy z těchto analýz následně tvoří návrhy na zlepšení.

This bachelor´s thesis deals with proposal to improve the company´s marketing mix, specifically the Hotel Červenohorské sedlo. In the theoretical part, the terms marketing mix, marketing, marketing environment, SWOT analysis and Porter´s analysis are clarified. In the analytical part, the hotel itself is described, and analyzes of the marketing environment in which hotel is located are also carried out. Furthermore, SWOT analzes and Porter´s analysis are performer. The outputs from these analyzes subsequently from proposal for improvement.
Proposal to improve the marketing mix of the company
Keywords: Marketing; marketingový mix; marketingové prostředí; SWOT analýza; Porterova analýza; hotel.; Marketing; marketing mix; marketing environment; SWOT analysis; Porter´s analysis; hotel.